Whole-genome comparative analysis at the lineage/sublineage level discloses relationships between Mycobacterium tuberculosis genotype and clinical phenotype - Negrete-Paz,Andrea Monserrat; Vázquez-Marrufo,Gerardo; Vázquez-Garcidueñas,Ma. Soledad (PeerJ, 2021)
Background Human tuberculosis (TB) caused by members of the Mycobacterium tuberculosis complex (MTBC) is the main cause of death among infectious diseases worldwide. Pulmonary TB (PTB) is the most common clinical phenotype of the disease, but some patients develop an extrapulmonary (EPTB) phenotype in which any organ or tissue can be affected. MTBC species include nine phylogenetic lineages, with some appearing globally and others being geographically restricted. EPTB can or not have pulmonary involvement, challenging its diagnosis when lungs are not implicated, thus causing an inadequate treatment. Finding evidence of a specific M. tuberculosis genetic background associated with EPTB is epidemiologically relevant due to the virulent and multidrug-resistant strains isolated from such cases. Until now, the studies conducted to establish associations between M. tuberculosis lineages and PTB/EPTB phenotypes have shown inconsistent results, which are attributed to the strain predominance from specific M. tuberculosis lineages/sublineages in the samples analyzed and the use of low-resolution phylogenetic tools that have impaired sublineage discrimination abilities. The present work elucidates the relationships between the MTBC strain lineages/sublineages and the clinical phenotypes of the disease as well as the antibiotic resistance of the strains. Methods To avoid biases, we retrieved the raw genomic reads (RGRs) of all (n = 245) the M. tuberculosis strains worldwide causing EPTB available in databases and an equally representative sample of the RGRs (n = 245) of PTB strains. A multiple alignment was constructed, and a robust maximum likelihood phylogeny based on single-nucleotide polymorphisms was generated, allowing effective strain lineage/sublineage assignment. Results A significant Odds Ratio (OR range: 1.8–8.1) association was found between EPTB and the 1.1.1, 1.2.1, 4.1.2.1 and ancestral Beijing sublineages. Additionally, a significant association between PTB with 4.3.1, 4.3.3, and 4.5 and Asian African 2 and Europe/Russia B0/W148 modern Beijing sublineages was found. We also observed a significant association of Lineage 3 strains with multidrug resistance (OR 3.8; 95% CI [1.1–13.6]), as well as between modern Beijing sublineages and antibiotic resistance (OR 4.3; 3.8–8.6). In this work, it was found that intralineage diversity can drive differences in the immune response that triggers the PTB/EPTB phenotype.
Keywords: Pulmonary tuberculosis; Extrapulmonary tuberculosis; Drug resistance; Ancient sublineages; Modern sublineages; SNP